PENGARUH POLA ASUH PEMBINA ASRAMA TERHADAP KECERDASAN SPRITUAL SANTRIWATI DI PESANTREN MODERN PUTRI IMMIM MINASATE’NE PANGKEP - Andi Nur Zaizar; Sitti Nurkhaerah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2024)
This study aims to determine the influence of dormitory supervisor parenting on the spiritual intelligence of female students at the Modern Islamic Boarding School SMA Pesantren Putri IMMIM Minasate'ne Pangkep. This quantitative research uses an ex post facto method with a simple linear regression design. The population consists of 116 students, with a sample of 40 female students selected using simple random sampling. The research instruments are the dormitory supervisor parenting and spiritual intelligence scales. Data analysis techniques include descriptive statistical analysis and inferential statistical analysis. The results indicate that dormitory supervisor parenting at SMA Pesantren Modern Putri IMMIM Minasate'ne Pangkep falls into the moderate category with a percentage of 87.5%, while spiritual intelligence is also in the moderate category with a percentage of 90%. The calculation shows the t-value is greater than the t-table value (t-value > t-table = 11.49 > 1.685) at a 5% significance level, indicating an influence of dormitory supervisor parenting on spiritual intelligence at this school. This study implies that students should enhance their devotion to Allah Swt. and adhere to the school's regulations. For dormitory supervisors, it provides evaluation material for their parenting methods. For the school, it serves as evaluation material for the supervisors' parenting style and the spiritual intelligence of the students. Future researchers can use this study as a reference for researching the influence of dormitory supervisor parenting on spiritual intelligence